Assessment of scientific information for the Radiation Exposure Screening and Education Program : interim report (National Academies Press (US), 2003)
In response to a request from the Health Resources and Services Administration (HRSA), the National Research Council convened a committee to assess the recent biologic, epidemiologic, and related scientific evidence associating radiation exposure with cancers or other human health effects. HRSA requested that the National Research Council committee provide an interim report to the agency and its grantees as preliminary guidance on the conduct of the ongoing and proposed activities. This interim report is based on the committee's review and assessment of the HRSA Bureau of Primary Health Care (BPHC) Policy Information Notice 2002-173 and its current grantees' proposals. It provides the committee's findings related to the most recent scientific information about radiation exposure and cancer and advice on improving access and quality of screening, education, and referrals. The intent of this interim report is to assist the Radiation Exposure Screening and Education Program (RESEP) staff to develop an action plan that is consistent with best medical and educational practices and the current state of science. The potential impact of recent developments in radiation dosimetry, radiation biology, and radiation epidemiology on the risk-assessment process is discussed for the purposes of establishing whether the Radiation Exposure Compensation Act populations are likely to be at greater or less risk of cancer as the result of prior exposure to radiation than is currently estimated.